A comparison of CEO pay–performance sensitivity in privately-held and public firms - Gao, Huasheng (2016)
In this paper we study CEO contract design employing a unique dataset on privately-held and public firm CEO annual compensation over the period 1999–2011. We first show that CEOs in public firms are paid 30% more than CEOs in comparable privately-held firms. We further show that both private and public firm CEO pays are positively and significantly related to firm accounting performance, and that the pay–performance link is much weaker in privately-held firms. We then show that the above findings are robust to accounting for firms' self-selection into being privately-held, and a number of important differences between privately-held and public firms, including CEO ownership, employee stock ownership, stock liquidity, discipline from the takeover market, and the availability of different performance measures. Overall, our results support the view that concentrated ownership substitutes for CEO performance-based compensation contracts.